2021
DOI: 10.1016/j.heliyon.2021.e07850
|View full text |Cite
|
Sign up to set email alerts
|

Build-up of labile, non-labile carbon fractions under fourteen-year-old bamboo plantations in the Himalayan foothills

Abstract: Carbon fractions under different bamboo species viz ., Bambusa balcooa, Bambusa bambos, Bambusa nutans, Dendrocalamus hamiltonii, Dendrocalamus asper and Dendrocalamus strictus were evaluated to understand the potential of these different bamboo species in soil rehabilitation in Himalayan foothills. The highest accumulation of the different carbon fractions likes very labile (6.12 mg g −1 ), less labile (2.55 mg g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 36 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, higher CMI value under bamboo plantation was also reported. 25 Also, lowest CMI value in soil stratum (0-20 cm) indicates that intensive soil management practices results in soil quality decline. CMI is a sensitive and helpful index for evaluating soil organic carbon dynamics over varied landuse.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, higher CMI value under bamboo plantation was also reported. 25 Also, lowest CMI value in soil stratum (0-20 cm) indicates that intensive soil management practices results in soil quality decline. CMI is a sensitive and helpful index for evaluating soil organic carbon dynamics over varied landuse.…”
Section: Discussionmentioning
confidence: 99%
“…Bamboo is a highly effective species for soil C sequestration (Nath et al 2015a) and it was found that soil C pools varied significantly after bamboo plantation. Kaushal et al (2021) reported that variation in soil C pools is mainly due to the abundant fine root biomass production and its subsequent decomposition. Moreover, the presence of high litter debris maintains the supply of easily decomposable C compounds and microbial population (Kaur et al 2008;Benbi et al 2015).…”
Section: Different Soil C Poolsmentioning
confidence: 99%
“…Worldwide, about 1500 species of bamboo from 75 to 107 genera have been reported (Ohrnberger 1999) and India is the second country after China in bamboo genetic resources, with around 136 species belonging to 23 genera (IFSR 2017). The estimated area coverage of bamboo in India is about 15.69 million ha (Kaushal et al 2021). Bamboo is known to provide various environmental benefits such as wind breaks, construction and timber materials, fuel wood, rehabilitation of degraded lands for erosion control and watershed protection (INBAR 2010;Nath et al 2015a;Mishra et al 2014).…”
Section: Introductionmentioning
confidence: 99%